Phytochemical screening and evaluation of hypoglycemic activity of citrus sinensis peel extract - Akbar, Nusrat (BRAC Univeristy, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2015.